Management of Patients With High Baseline Hip Fracture Risk by FRAX Reduces Hip Fractures—A Post Hoc Analysis of the SCOOP Study. (23rd March 2018) - McCloskey, Eugene; Johansson, Helena; Harvey, Nicholas C; Shepstone, Lee; Lenaghan, Elizabeth; Fordham, Ric; Harvey, Ian; Howe, Amanda; Cooper, Cyrus; Clarke, Shane; Gittoes, Neil; Heawood, Alison; et al.
ABSTRACT: The Screening for Osteoporosis in Older Women for the Prevention of Fracture (SCOOP) study was a community‐based screening intervention in women aged 70 to 85 years in the United Kingdom. In the screening arm, licensed osteoporosis treatments were recommended in women identified to be at high risk of hip fracture using the FRAX risk assessment tool (including bone mineral density measurement). In the control arm, standard care was provided. Screening led to a 28% reduction in hip fractures over 5 years. In this planned post hoc analysis, we wished to examine for interactions between screening effectiveness on fracture outcome (any, osteoporotic, and hip fractures) on the one hand and baseline FRAX 10‐year probability of hip fracture on the other. All analyses were conducted on an intention‐to‐treat basis, based on the group to which women were randomized, irrespective of whether screening was completed. Of 12, 483 eligible participants, 6233 women were randomized to screening, with treatment recommended in 898 (14.4%). No evidence of an effect or interaction was observed for the outcomes of any fracture or osteoporotic fracture. In the screening arm, 54 fewer hip fractures were observed than in the control arm (164 versus 218, 2.6% versus 3.5%), and commensurate with treatment being targeted to those at highest hip fracture risk, the effect on hip fracture increased with baseline FRAX hip fracture probability ( p = 0.021 for interaction); for example, at the 10th percentile of baseline FRAX hip probability (2.6%), there was no evidence that hip fractures were reduced (hazard ratio [HR] = 0.93; 95% confidence interval [CI] 0.71 to 1.23), but at the 90th percentile (16.6%), there was a 33% reduction (HR = 0.67; 95% CI 0.53 to 0.84). Prior fracture and parental history of hip fracture positively influenced screening effectiveness on hip fracture risk. We conclude that women at high risk of hip fracture based on FRAX probability are responsive to appropriate osteoporosis management. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc.